2018
DOI: 10.1002/ajp.22863
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermal imaging: Positive and negative emotions modify the skin temperatures of monkey and ape faces

Abstract: Facial thermography has enabled researchers to noninvasively and continuously measure the changes of a range of emotional states in humans. The present work used this novel technology to study the effect of positive and negative emotions in nonhuman primates by focusing on four facial areas (the peri-orbital area, the nose bridge, the nose tip, and the upper lip). Monkeys and apes were examined for positive emotions (during interactions with toys and during tickling) and for negative emotions (during food dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 42 publications
2
45
0
1
Order By: Relevance
“…Although more research has focused on measuring temperature decreases during increased arousal, blood flow changes corresponding to increased forehead temperatures have been observed in humans during relaxing activities such as meditation [54]. Measuring temperature in multiple locations, as suggested by Chotard et al [55], and examining the changes observed in conjunction with one another may help to tease apart some of these conflicting results. It is also possible that in the case of these three gorillas, the interactions themselves did not result in emotional changes and that the differences seen in nasal temperatures are reflective of other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although more research has focused on measuring temperature decreases during increased arousal, blood flow changes corresponding to increased forehead temperatures have been observed in humans during relaxing activities such as meditation [54]. Measuring temperature in multiple locations, as suggested by Chotard et al [55], and examining the changes observed in conjunction with one another may help to tease apart some of these conflicting results. It is also possible that in the case of these three gorillas, the interactions themselves did not result in emotional changes and that the differences seen in nasal temperatures are reflective of other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Coupled with drone technology, infrared thermography has been used to provide population estimates by detecting animal heat-signatures in remote, difficult-tonavigate locations (Kays et al, 2018;Spaan et al, 2019;Burke et al, 2019). Facial infrared thermal imaging has been used to quantify the emotional states of non-human primates (Nakayama, Goto, Kuraoka, & Nakamura, 2005;Kuraoka & Nakamura, 2011;Ioannou, Chotard, & Davila-Ross, 2015;Chotard, Ioannou, & Davila-Ross, 2018) and other animals (McCafferty, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Both positive and negative emotions activate ANS responses, which subsequently lead to physiological changes associated with alterations of blood flow, leading to surface temperature fluctuations (Sinha et al, 1992;Collet et al, 1997;Chotard et al, 2018).…”
Section: Superficial Temperaturementioning
confidence: 99%
“…Due to the recent advances in thermal imaging technology and its noninvasive noncontact nature, the use of portable infrared cameras in animal emotion assessment research has been gaining popularity (e.g., Nakayama et al, 2005 ; Stewart et al, 2005 , 2007 , 2008 , 2011 , 2017 ; Kuraoka and Nakamura, 2011 ; Valera et al, 2012 ; Bartolomé et al, 2013 ; Herborn et al, 2015 ; Proctor and Carder, 2015 ; Cannas et al, 2018 ; Chotard et al, 2018 ; Hussein, 2018 ; Redaelli et al, 2019 ).…”
Section: Positive-emotion Assessment In Dogsmentioning
confidence: 99%